Blockchain and Public Record Keeping: Of Temples, Prisons, and the (Re)Configuration of Power - Lemieux, Victoria L. (Frontiers in Blockchain, 2019)
This paper discusses blockchain technology as a recordkeeping system, linking recordkeeping to power of authority, veneration (temples) and control (prisons) that configure and reconfigure social, economic and political relations. It discusses blockchain technology as being constructed as a mechanism to counter institutions and social actors that currently hold power, but whom are nowadays often viewed with mistrust. It explores claims for blockchain as a recordkeeping force of resistance to those powers. Using an archival theoretic analytic lens, the paper evaluates claims that blockchain technology can support the creation and preservation of trustworthy records able to serve as alternative sources of evidence of rights, entitlements and actions than that which is provided by centralized public repositories of records, such as archives and public registries. The analysis problematizes such claims, pointing to shortcomings in the design, implementation and governance of blockchain platforms that fall short of the ideal of trustworthy public recordkeeping, but suggesting that through unveiling these weaknesses, it may be possible for blockchain recordkeeping to address the ills of current, centralized approaches to public recordkeeping.